Exploring the Factors that Influence Pivoting in Student Startups: A Case Study of Entrepreneurship Student of SBM ITB Analysis - Esther Ariella (Jurnal Syntax Transformation, 2023)
According to recent news sources and journals, the growth of start-ups in today's world is on the rise. The pandemic has played a significant role in this growth, with many people starting their own businesses after being laid off from their jobs (Casselman, 2021). In 2023, experts predict that there will be increased investment in social media, user-generated content, and entertainment for small businesses (Halperin, 2023). Alternative funding sources are also becoming more common for small businesses as interest rates rise (Halperin, 2023). The design acts as the research project's "blueprint," connecting the design, data collecting, and analytic activities to the research questions and guaranteeing that the entire study agenda will be covered. Based on the tentative coding analysis that has been done above to answer the question "what encourages you to pivot?", that have been analyzed into selective coding, it can be seen that their reason is because their own ability to build a business is still not that enhanced. This conclusion could be argued because there are severals variable that are supporting the conclusion. For example the informant said that the lack of proper planning, difficult process to execute, and the customer is not interested in the idea offered are the reason that prompting the pivoting phenomenon. Based on the results of the research conducted, it can be seen that as many as 17 out of 20 student startups in the SBM ITB entrepreneurship department experienced pivoting. The majority of these student startups experience pivoting in their business model and business ideas, where the pivoting they experience is included in the types of pivoting discussed in the previous chapter such as technology, customer need, customer segment, channel, complete, and side project types.